2012
DOI: 10.1002/glia.22407
|View full text |Cite
|
Sign up to set email alerts
|

Decreased vulnerability of hippocampal neurons after neonatal hypoxia–ischemia in bis‐deficient mice

Abstract: The Bcl-2-interacting death suppressor (Bis) protein is involved in antiapoptosis and antistress pathways. However, its roles after neonatal hypoxia-ischemia remain obscure. Therefore, we investigated the effects of Bis deletion on hippocampal cell death following neonatal hypoxia-ischemia. We transected the right common carotid artery of bis(+/+) and bis(-/-) mice at postnatal Day 7 and subjected them to hypoxia for 35 min. Cresyl violet staining showed that hypoxia-ischemia induced progressive cell death in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…We found early changes in D f ADC contrasts in the Py cell layer of the hippocampal CA1 region (at 24 h post-HI), with relatively delayed onset of changes observed in the GrDG layer. HI has been previously shown to lead to selective cell death of CA1 pyramidal neurons and granule cells in the dentate gyrus in the neonatal mouse brain, at 24-72 h following injury (9,41,42). In our study, compared with the Py region, significant differences in D f ADC measurements between the ipsilateral and contralateral GrDG regions were first detected at day 4 after HI-injury.…”
Section: Discussionsupporting
confidence: 49%
“…We found early changes in D f ADC contrasts in the Py cell layer of the hippocampal CA1 region (at 24 h post-HI), with relatively delayed onset of changes observed in the GrDG layer. HI has been previously shown to lead to selective cell death of CA1 pyramidal neurons and granule cells in the dentate gyrus in the neonatal mouse brain, at 24-72 h following injury (9,41,42). In our study, compared with the Py region, significant differences in D f ADC measurements between the ipsilateral and contralateral GrDG regions were first detected at day 4 after HI-injury.…”
Section: Discussionsupporting
confidence: 49%
“…The neonatal hypoxic-ischemic brain injury model used in this study was adapted from the method described by Rice et al [ 25 ], with minor modifications. It is a widely used neonatal stroke model, and has been employed to explore drug intervention targets for neonatal hypoxic-ischemic brain injury [ 26 , 27 ]. We have established this HI model to study the neuroprotective effects of a volume-regulated anion channel blocker [ 28 ] and hypoxic preconditioning [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We, and other groups, have reported that Bis expression is increased by oxidative stress or pro-oxidants, both in vivo and in vitro [ 20 , 27 , 28 ]. The physiological significance of Bis induction upon PDTC or HNE was verified by the knockdown of HSF1 [ 20 , 21 ], showing that HSF1-mediated Bis expression confers cellular protection from pro-apoptotic and inflammatory stress.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a HSF1 deficiency or inactivation may result in a significant impairment in the antioxidant system, through the modulation of Bis expression and subsequent SOD. However, the survival of neuronal cells of the hippocampus following neonatal hypoxia-reperfusion was higher in bis-deleted (bis -/- ) mice than in the wild type (bis +/+ ) mice, possibly because of the modulation of galectin 3 levels [ 28 ]. Taken together, these results suggest that the modulation of Bis expression resulted in diverse effects related to cell survival depending on the cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation